"Pick your team wisely": A case study of a long-standing research-practice partnership. (December 2022) - Melton, Theresa N.; Agans, Jennifer P.; Lawhon, Ben; Mateer, Timothy J.; Freeman, Stephanie; Taff, B. Derrick
Abstract: Research-practice partnerships (RPP) provide opportunities to connect researchers, practitioners, and/or community development professionals in meaningful ways, thereby improving the quality of research, evaluation, and practice in communities. Yet, there is still much to learn about how successful partnerships between researchers and practitioners develop. Historically, research on this topic has emphasized challenges that prevent RPP from developing to their highest potential, with limited information available on ways to promote RPP and how to ensure RPP are mutually beneficial for participants. However, research on partnerships more generally, such as multisector partnerships, can contribute meaningfully to the RPP field. We present an in-depth case study on a successful, long-term partnership. In this study, we pull from the broader partnership literature to explore contexts that are likely to promote partnerships, as well as the activities that can strengthen RPP. Findings focus on addressing ways to promote RPP and highlight the importance of preexisting factors, such as a culture that values both researcher and practitioner expertise, history, and chemistry between partners. Additionally, non-professional space and time, productive disagreements, clear but evolving roles, and shared power were found to strengthen collaboration within the partnership. Specific advice for anyone considering joining an RPP is also discussed. Highlights: Research-practice partnerships can connect researchers and practitioners in meaningful ways. This paper provides an in-depth analysis of a long-standing, successful partnership. It is important for researchers and organization executives to value applied research. Non-professional space and time, productive disagreements, clear but evolving roles, and shared power also strengthened the partnership. Participants recommend ensuring alignment in both mission and goals early on.